Healing and Salvation in Late Modernity: the Use and Implication of Such Terms in the Ecumenical Movement - Horsfjord, Vebjørn L. (International review of mission, 2007)
This article explores developments over the last decades in the way ecumenical texts, primarily originating from world conferences organized by the Commission on World Mission and Evangelism, speak about soteriology. Under the headlines, “Salvation Today” (1973) and “Your Kingdom Come” (1980), terminology inspired by liberation theology took centre stage, and a predominantly immanent understanding of salvation was promoted. In recent years a different terminology has taken over, and it is one that focuses on “healing” and “the fullness of life”. At its best, the holistic healing approach manages to take up the important concerns from earlier times, such as economic justice, racism and environmental issues, while at the same time giving more room for existential issues and the experiences of the individual The new healing discourse appears to reflect two different modalities of the church's healing ministry, viz. that which is concerned with the causes of suffering, and that which addresses the experience of suffering. The latter was often ignored in the recent past. The healing discourse gives room for new explorations of practices that have been central in the church throughout its history, such as anointing the sick, and praying for and with them, and hearing individual confessions. Openness towards subjective experience also has implications for the contextualization of the Christian faith. There is a new awareness that not only do the causes of suffering vary from situation to situation but so does the understanding of (what constitutes) suffering itself. Changing or varying understandings of suffering give rise to different approaches to its alleviation, and can inspire a rethinking of how we understand salvation in different contexts. The new healing discourse can also be studied in its relationship to cultural trends known as post-modernity or late modernity. The texts under study display very ambivalent approaches to these developments. There might be a tendency for texts that have concrete experience as their starting point to take a more positive view of these cultural developments than do texts that begin with more general theological observations.